If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 4 = 3x + -6 Reorder the terms: 4 + 4x = 3x + -6 Reorder the terms: 4 + 4x = -6 + 3x Solving 4 + 4x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + 4x + -3x = -6 + 3x + -3x Combine like terms: 4x + -3x = 1x 4 + 1x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 4 + 1x = -6 + 0 4 + 1x = -6 Add '-4' to each side of the equation. 4 + -4 + 1x = -6 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = -6 + -4 1x = -6 + -4 Combine like terms: -6 + -4 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| 1.29x=c | | 0.99x+21=c | | -t^2+2t+24=0 | | x-(6x-2)=-10x+(5-x) | | x-.1x=120 | | -16t^2+32t+284=0 | | 2a+3b=21 | | 0x+1x=0x | | a=b-2 | | 0.67x+0.83=20-4x | | -0.3x=6 | | x^2(400-2x^2/3x) | | X^2-5x-10=o | | x^2-6x-160=0 | | 3X-4=4X+20 | | x^2+x^3=2 | | 10x+15y=1000 | | 6x-2=2x | | -3+x/-8+2 | | (x+9)+30+(180-(2x+3))=180 | | b(2b+1)=36 | | 1/2(x+2)(3x-14)=(x+2)(x+2) | | 4x^2+18x+24=0 | | 2(t+3)=t(t+7) | | -55+X=100 | | 5-2(x-1)=4-x | | 5(3y-4)-3(2y+1)= | | x+(-47)=-37 | | 10x+15=12x-1 | | 52/12-17/10+3/4 | | 7x+3=30-2x | | 7/12k=I |